1997
DOI: 10.1111/j.1432-1033.1997.t01-2-00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase β, a Putative Type‐2A Protein Phosphatase from the Human Malaria Parasite Plasmodium Falciparum

Abstract: Protein phosphatases play a critical role in the regulation of the eukaryotic cell cycle and signal transduction. A putative protein serinehhreonine phosphatase gene has been isolated from the human malaria parasite Plasmodium fulciparum. The gene has an unusual intron that contains four repeats of 32 nucleotides and displays a high degree of size polymorphism among different strains of P. fulciparum. The open reading frame reconstituted by removal of the intron encodes a protein of 466 amino acids with a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…Hence, the investigation of phosphatase regulatory proteins in parasites may constitute an additional step towards a better understanding of the signalling pathways and the discovery of potential therapeutic targets. In P. falciparum extracts, Ser/Thr phosphatase activities (PP1, 2A, 2B, 2C) have been detected, leading subsequently to the molecular characterization of all these phosphatases (Li and Baker, 1997;Mamoun et al, 1998;Baker and Li, 1999; Immunoblot analysis of eluates from oocyte extracts after binding to microcystin beads, revealed either by anti-PP1 antibodies or by anti-V5 antibodies. The first two panels correspond to cRNA PfLRR1-injected oocyte eluates, and the last two panels correspond to eluates of buffer-injected oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the investigation of phosphatase regulatory proteins in parasites may constitute an additional step towards a better understanding of the signalling pathways and the discovery of potential therapeutic targets. In P. falciparum extracts, Ser/Thr phosphatase activities (PP1, 2A, 2B, 2C) have been detected, leading subsequently to the molecular characterization of all these phosphatases (Li and Baker, 1997;Mamoun et al, 1998;Baker and Li, 1999; Immunoblot analysis of eluates from oocyte extracts after binding to microcystin beads, revealed either by anti-PP1 antibodies or by anti-V5 antibodies. The first two panels correspond to cRNA PfLRR1-injected oocyte eluates, and the last two panels correspond to eluates of buffer-injected oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic activities and genes related to plasmodial phosphatases (PPs) have been identified. These include PfPP1, PfPP2A, PfPP2B and PfPP2C (Li and Baker, 1997;1998;Mamoun et al ., 1998;Dobson et al ., 1999;Bhattacharyya et al ., 2002;Kumar et al ., 2002). The PfPP1 protein sequence (Bhattacharyya et al ., 2002) possesses the signature of Ser/Thr phosphatase LRGNHE, as well as two putative protein kinase C and five putative casein kinase II phosphorylation sites.…”
Section: Introductionmentioning
confidence: 99%
“…The first step of protein heating was skipped, and the nickel affinity-purified protein was directly exchanged against the NMR buffer (PD10, G-25 desalting resin, GE Healthcare) and concentrated using centrifugal devices. NMR buffer is 25 mM Tris-d 11 , pH 6.8, 25 mM NaCl, 2.5 mM EDTA, 1 mM d 4 -trimethylsilyl propionate as proton chemical shift internal reference, and 5% D 2 O. Additionally, 1 mM of tri-(hydroxypropyl) phosphine was used as reductor in the three-dimensional experiments that required several days of data acquisition, whereas 2.5 mM dithiothreitol (DTT) was used for two-dimensional { 1 H, 15 N}HSQC. Proteins in NMR buffer were at 250 M for the three-dimensional experiment series and 100 M for two-dimensional { 1 H, 15 N} HSQC.…”
Section: Methodsmentioning
confidence: 99%
“…In Plasmodium falciparum (Pf), an apicomplexan parasite responsible for most of the morbidity and mortality attributable to human malaria, phosphatase activities and corresponding genes have been identified, including PP1 and PP2A (12)(13)(14)(15)(16)(17). The use of natural toxins to phosphatases, such as okadaic acid, indicated that blood stage parasites exhibited a high level of phosphatase activity associated with PP1 (14).…”
mentioning
confidence: 99%
“…PP2A localizes to and regulates microtubule dynamics in a variety of cell types and its localization changes upon various stimuli [14][15][16][17][18]. Moreover, PP2A is involved in differentiation of Trypanosoma cruzi and Plasmodium falciparum [19][20][21]. Therefore, we asked whether PP2A-C might localize to unique elements of the giardial cytoskeleton and be an important mediator of its differentiation.…”
Section: Introductionmentioning
confidence: 99%